Increasing the ability to discuss science subjects through the application of the jigsaw method - Tirahmah, Tirahmah; Yati, Yati (Panicgogy International Journal, 2024)
The research titled "Increasing the Discussion Ability of Science Subjects through the Application of the Jigsaw Method for Class VI Students at SDN 8 Steps in 2022" conducted at SDN 8 Langkahan, Langkahan Regency, aimed to enhance the discussion skills of Class VI students using the Jigsaw Method. This method was chosen for its effectiveness in promoting collaborative learning and active participation among students. Classroom Action Research was employed as the research methodology, involving 30 teachers at SDN 8 Langkahan. The research design adhered to the principles outlined by Kemmis and McTaggart. Data was collected through various methods including observation, field notes, and documentation. The analysis of the data implemented descriptive statistics to gauge the effectiveness of the Jigsaw Method in improving discussion skills. The findings revealed a significant increase in the average discussion ability score from before cycle I to cycle II. Specifically, there was an impressive rise from an initial score of 45 to 68.94 after the second cycle, indicating a substantial improvement of 23.94 points. These results underscore the efficacy of the Jigsaw Method in fostering enhanced discussion abilities among Class VI students at SDN 8 Langkahan. By actively engaging students in collaborative learning experiences, the method not only enhances their understanding of science subjects but also cultivates vital communication and teamwork skills essential for their academic and personal development.